“Education, empire and the heterogeneity of investigative modalities”: a reassessment of colonial surveys on indigenous Indian education - Kakkar, Ankur (Paedagogica historica, 2017)
As the British expanded their dominions in India, political and administrative needs made it imperative for them to acquire more information about their subjects. Hence, systematic and meticulous surveys began to be commissioned by the East India Company as it assumed charge of educating the natives. These surveys were an integral part of what Bernard Cohn has called the “documentation project” whose ultimate object was to control and subjugate the colonial subjects. Therefore, a key purpose of instituting educational surveys was to dismiss indigenous education and justify its supersession by colonial education. In the process, much of the information acquired by the colonial state was simplified and digested into a monolithic narrative. This article shows that regardless of the imperatives that influenced it, the colonial survey sometimes revealed fascinating details about the nature of indigenous institutions that were often overlooked by the British Governors General. As a case study, this article examines a set of enquiries instituted by the governments of Madras, Bombay, and Bengal in 1822, 1824, and 1835 respectively. By re-examining the reports submitted by district collectors in response to these government enquiries, this article seeks to challenge colonial notions about indigenous education. One of the principal aims of this article is to refute the charge that indigenous schools did not impart any moral or useful instruction. In doing so, the article also aims to highlight the instruction that was imparted in indigenous schools.
Published online: 08 Januar 2017
Gesehen am 14.07.2018
Keywords: Geschichte 1835-1935; Großbritannien; Indien